2021
DOI: 10.3389/fpls.2021.764103
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of Nitrogen, Phosphorus, and Potassium for Soilless Production of Cannabis sativa in the Flowering Stage Using Response Surface Analysis

Abstract: Following legalisation, cannabis has quickly become an important horticultural crop in Canada and increasingly so in other parts of the world. However, due to previous legal restrictions on cannabis research there are limited scientific data on the relationship between nitrogen (N), phosphorus (P), and potassium (K) supply (collectively: NPK) and the crop yield and quality. This study examined the response of a high delta-9-tetrahydrocannabinol (THC) Cannabis sativa cultivar grown in deep-water culture with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 30 publications
(49 reference statements)
2
42
0
Order By: Relevance
“…The remaining N was supplied as N-NO 3 – , to a final uniform level of 200 mg L –1 N in all treatments. This level was previously demonstrated to be within the optimal range for medical cannabis cultivation ( Bevan et al, 2021 ; Saloner and Bernstein, 2021 ). Throughout the remainder of the experiment, the plants were cultivated under a short photoperiod (12/12 h light/dark) for the induction of inflorescence development.…”
Section: Methodsmentioning
confidence: 64%
See 2 more Smart Citations
“…The remaining N was supplied as N-NO 3 – , to a final uniform level of 200 mg L –1 N in all treatments. This level was previously demonstrated to be within the optimal range for medical cannabis cultivation ( Bevan et al, 2021 ; Saloner and Bernstein, 2021 ). Throughout the remainder of the experiment, the plants were cultivated under a short photoperiod (12/12 h light/dark) for the induction of inflorescence development.…”
Section: Methodsmentioning
confidence: 64%
“…Boron and Mo were added from the fertilizers B-7000 and Bar-Koret, respectively (Israel chemicals, Tel-Aviv, Israel). The concentrations of the three major macronutrients used for fertigation in the present study (200 mg L –1 N, 60 mg L –1 P, and 100 mg L –1 K), were selected to be within the optimal range for medical cannabis plant development and function, following on previous studies that reported plant responses to a range of supply rates ( Saloner et al, 2019 ; Bevan et al, 2021 ; Saloner and Bernstein, 2021 ; Shiponi and Bernstein, 2021b ). The irrigation solution was made once weekly and the pH of the solution was adjusted to 5.6–6.0.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of optimizing indoor systems has increased due to the demand for yield maximization and improved efficiency of growing systems [ 13 ]. Final yield quantity and quality of inflorescences are highly variable and depends on numerous factors such as genotype [ 14 , 15 , 16 ]; the agronomic practices, such as irrigation and fertilizer regimes [ 17 , 18 , 19 , 20 ], light spectra [ 14 , 21 ], intensity [ 22 , 23 ] and photoperiod [ 24 ]; plant density [ 25 ]; environmental conditions (humidity and temperature) [ 12 ] and the influence of biotic and abiotic stresses [ 26 , 27 ]—including pruning and defoliation techniques [ 28 , 29 ]—and finally, the duration of the vegetative and generative period. Thus, so many differences can be found for reported yield of medicinal cannabis currently in literature.…”
Section: Introductionmentioning
confidence: 99%
“…It was simple and easy to implement but could not be comprehensive enough to investigate the interaction of each factor [ 19 ]. RSM is another empirical modeling technique that allowed simultaneous optimization of multiple factors on a larger scale with fewer test units than traditional designs [ 22 ]. It not only saved lots of times and resources but also accounted for the interaction of experimental factors.…”
Section: Discussionmentioning
confidence: 99%